The primitive extratesticular seminoma: diagnosis of a rare pathology - Saba, Luca (Acta Biomedica Atenei Parmensis, 2017)
Background: The Primitive Extratesticular Seminoma is a very rare condition and represents 3% of germ cell tumors; it is an indeterminate origin disease, whose diagnosis is often complicated by a nonspecific and highly variable clinical finding. Case presentation: A caucasian 55 years old male, non-smoker, arrived to our centre with cough, severe respiratory distress and dysphagia, in a context of the superior vena cava syndrome. A Computed Tomography was performed, which shows the presence of a mediastinal anterior mass with aorto-pulmonary window and left paracardiac invasion. A biopsy of the mediastinal mass was performed with mediastinoscopy; the hystological diagnosis was seminoma. After, first of all the 18FDG PET-CT is performed, which shows the presence of an intense hypermetabolism (SUV max=20.3 and metabolic volume 867 cc) at the level of bulky mediastinal mass, with paratracheal, aorto-pulmonary window and left paracardiac invasion. The mass presents also a sternal manubrium invasion. There were no other detectable tissue metabolic alterations with the 18FDG PET-CT and, in particular, the testicles examination was negative. A bilateral testicular ultrasound (US) was executed, which confirms the absence of testicular germ tumor. Clinical laboratory tests show a significant increase of beta-HCG (123 IU/L); AFP is negative. A final diagnosis of primitive extratesticular seminoma was carried. Conclusions: The Primitive Extratesticolar Seminoma is a rare patology, and, for its massive size at the onset diagnosis, curable in early stage often only with radiochemotherapy. The Diagnostic Imaging and Nuclear Medicine, as Testicular Ultrasound, the CT with contrast medium and the 18FDG PET-CT total body examination, are fundamental to the staging and localisation. MRI sometimes is useful for testicular evaluation. The biopsy is needed for tissue characterization.